The principle of association in the use of the definite article in English and Swedish - Budziszewski, Arkadiusz (Folia Scandinavica Posnaniensia, 2007)
In the first part of the paper the mechanism of association in the use of the definite article is presented. The author also accounts for the most common types of relations between things associated with each other. In the remaining part, the use of the principle of association in English noun phrases is discussed. The author demonstrates that there is a formal difference between the two languages in the way of expressing the definiteness of a referent.